The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1128/jcm.00360-07
|View full text |Cite
|
Sign up to set email alerts
|

Reclassification of Phenotypically Identified Staphylococcus intermedius Strains

Abstract: To reclassify phenotypically identified Staphylococcus intermedius strains, which might include true S. intermedius strains and novel species such as Staphylococcus pseudintermedius and Staphylococcus delphini, we analyzed molecular phylogenies and phenotypic characteristics of 117 S. intermedius group (SIG) strains tentatively identified as being S. intermedius by the Rapid ID32 Staph assay. From phylogenetic analyses of sodA and hsp60 sequences, the SIG strains were divided into three clusters, which belonge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
248
2
11

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(272 citation statements)
references
References 39 publications
11
248
2
11
Order By: Relevance
“…E. coli isolates from diarrheic pigs in Korea [16] had a higher frequency of resistance to tetracycline (97.1%) and streptomycin (99%), while the rate of resistance to ampicillin (27.1%) was comparable to our investigation. A moderate to high level resistance to these antibacterial agents was also reported for E. coli strains isolated from feces of healthy dogs [5], cattle and pigs [20,25].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…E. coli isolates from diarrheic pigs in Korea [16] had a higher frequency of resistance to tetracycline (97.1%) and streptomycin (99%), while the rate of resistance to ampicillin (27.1%) was comparable to our investigation. A moderate to high level resistance to these antibacterial agents was also reported for E. coli strains isolated from feces of healthy dogs [5], cattle and pigs [20,25].…”
mentioning
confidence: 99%
“…S. pseudintermedius is the principal cause of pyoderma and otitis in canine [24]. Although it had been misidentified for decades as S. intermedius, recent analyses by molecular phylogenetic and PCR-restriction fragment length polymorphism (PCR-RFLP) approaches indicated that S. pseudintermedius, not S. intermedius, is the major canine pyoderma pathogen [6,23,25], and it has already been proposed that all strains from dogs identified by traditional means be reported as S. pseudintermedius [6,11]. Increasing resistance of this organism and failures to treat canine pyoderma or otitis with a number of antibacterial agents, including fluoroquinolones were reported recently [6,30].…”
mentioning
confidence: 99%
“…?show "fnote_aff1"$^! "content-markup(./author-grp [1]/aff|./author-grp [1]/dept-list)> Staphylococcus pseudintermedius, previously identified as Staphylococcus intermedius, 9,10,20 is the most common etiologic agent in canine pyoderma 21 and an agent commonly involved in canine otitis. 17,22 Methicillin-resistant S. pseudintermedius (MRSP) has been increasingly reported as a primary pathogen in canine infections.…”
mentioning
confidence: 99%
“…Subsequently, this species was also found in a wide range of animals, including horses, mink, domestic pigeons, and recently it was isolated from donkeys (Hesselbarth and Schwarz 1995, Futagawa-Saito et al 2006, Futagawa-Saito et al 2007, Sledge et al 2010, Gharsa et al 2014. The phylogenetic analysis of nuc gene sequences revealed, that this species is formed by two genetically distinct groups (A and B) (Sasaki et al 2007). Moreover, DNA-DNA hybridization results showed, that S. delphini group A isolates were distinguished from S. delphini group B, S. intermedius, and S. pseudintermedius isolates.…”
mentioning
confidence: 99%
“…The nuc gene sequences analysis showed that isolates belonging to S. delphini group B are more related to the reference S. pseudintermedius LMG 22219(T) than to S. delphini LMG 22190(T). However, phenotypic properties to differentiate S. delphini group A, S. delphini group B, and S. pseudintermedius were not found (Sasaki et al 2007). Mustelidae such as minks, ferrets, and badgers are regarded as natural hosts of S. delphini group A .…”
mentioning
confidence: 99%